2022
DOI: 10.23917/mesin.v23i2.19347
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat Treatment and Pressing at 400 °c With Coconut Shell Charcoal Media on the Hardness, Microstructure, and Density of Al-Si Alloys

Abstract: This study aims to determine the effect of the heat treatment process and pressing on hardness, density, and morphological changes in the microstructure of Al-Si alloys. In this study, the medium used was coconut shell charcoal with a mesh size of 80 at a heat treatment process of 400 °C and a holding time of 75 minutes. The pressing was carried out with a load of 150 N. The result of this research is an increase in the hardness of the Al-Si alloy with an average value of 133 VHN after the Heat Treatment and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, it is necessary to research the manufacture of permanent molds with FCD because it has hard dan tough properties, has a higher melting point than gray cast iron, and will be easy to machine to produce good products/molds and more precision to reduce the finishing process [18][19][20]. Hardness and toughness are important properties of metals [21][22][23][24][25]. The hardness and toughness of permanent molds with cast iron material are influenced by the percentage of roundness of graphite in the microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to research the manufacture of permanent molds with FCD because it has hard dan tough properties, has a higher melting point than gray cast iron, and will be easy to machine to produce good products/molds and more precision to reduce the finishing process [18][19][20]. Hardness and toughness are important properties of metals [21][22][23][24][25]. The hardness and toughness of permanent molds with cast iron material are influenced by the percentage of roundness of graphite in the microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the toughness of nodular cast iron can still be improved by modifying the microstructure. The microstructure can be changed by adding alloying elements or by heat treatment [14][15][16]. One of the most common heat treatments applied to increase the toughness of nodular cast iron is austempering.…”
Section: Introductionmentioning
confidence: 99%
“…After the use of Urbach Energy, it was found that the GO/Nd 2 O 3 composite might be used in electronic equipment using 0.050-0.063 eV semiconductor materials. Masyrukan et al [13] heated and pressed an Al-Si alloy using coconut shell charcoal as part of a study examined hardness, density, and microstructure morphology. Heat treatment was found to, on average, increase hardness to 133 VHN.…”
Section: Introductionmentioning
confidence: 99%